Accuracy of IOP Measured By Non-Contact (Air ? Puff) Tonometer Compared with Goldmann Applanation - , Zaheer-ud-Din Aqil Qazi, Javied Ahmad, Muhammad Rizwan Khan, Muhammad Naeem Azhar Tariq Mahmood Arain (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the frequency of accuracy of intraocular pressure (IOP) measured by non-contact (air puff) tonometer compared with Goldmann applanation tonometer. Material and Methods: This comparative study was done from April 2011 to September 2011, 286 patients between 10 to 72 years of age, both male and females coming to eye OPD for refraction and ocular examination included. Selected patients were explained and after informed consent; intraocular pressure was taken by consultant Ophthalmologist with Goldmann applanation tonometer (Haag – streit AT900) and Air puff tonometer (Keeler PT100) between 8 am to 1 pm. Results: Air puff tonometer had an overall accuracy of 49.70% to measure intraocular pressure within ± 2 mm Hg difference compared with Goldmann applanation tonometer. Air puff tonometer is more accurate at low pressure range, 54.40% at 10 – 20 mm Hg and accuracy decreases at higher pressure range, 20% at 51 – 60 mm Hg. At all ranges of intraocular pressures Air puff tonometer measured higher (mean 2.87 mm Hg) values than Goldmann applanation tonometer. Conclusion: Airpuff tonometer is quick, a non-contact method to measure intraocular pressure and is useful for screening purposes but the measurements should be confirmed with Goldmann applanation tonometer for accurate labelling of intraocular pressure.